Altered Sensory Neuron Development in CMT2D Mice Is Site-Specific and Linked to Increased GlyRS Levels - Sleigh, James N.; Mech, Aleksandra M.; Aktar, Tahmina; Zhang, Yuxin; Schiavo, Giampietro (Frontiers in Cellular Neuroscience, 2020)
Dominant, missense mutations in the widely and constitutively expressed GARS1 gene cause a peripheral neuropathy that usually begins in adolescence and principally impacts the upper limbs. Caused by a toxic gain-of-function in the encoded glycyl-tRNA synthetase (GlyRS) enzyme, the neuropathology appears to be independent of the canonical role of GlyRS in aminoacylation. Patients display progressive, life-long weakness and wasting of muscles in hands followed by feet, with frequently associated deficits in sensation. When dysfunction is observed in motor and sensory nerves, there is a diagnosis of Charcot-Marie-Tooth disease type 2D (CMT2D), or distal hereditary motor neuropathy type V if the symptoms are purely motor. The cause of this varied sensory involvement remains unresolved, as are the pathomechanisms underlying the selective neurodegeneration characteristic of the disease. We have previously identified in CMT2D mice that neuropathy-causing Gars mutations perturb sensory neuron fate and permit mutant GlyRS to aberrantly interact with neurotrophin receptors (Trks). Here, we extend this work by interrogating further the anatomy and function of the CMT2D sensory nervous system in mutant Gars mice, obtaining several key results: 1) sensory pathology is restricted to neurons innervating the hindlimbs; 2) perturbation of sensory development is not common to all mouse models of neuromuscular disease; 3) in vitro axonal transport of signalling endosomes is not impaired in afferent neurons of all CMT2D mouse models; and 4) Gars expression is selectively elevated in a subset of sensory neurons and linked to sensory developmental defects. These findings highlight the importance of comparative neurological assessment in mouse models of disease and shed light on key proposed neuropathogenic mechanisms in GARS1-linked neuropathy.